Academic Senate Minutes 2004-04-22 - Academic Senate:::::::::
Chair Report. Agenda – Approved. Minutes of 10/24/19 – Approved. President Report. Provost Report. Vice Chair Report. Associated Students Report. Statewide Senators Report. Emeritus Policy Revision – Second Reading – amended and approved. FSAC Report. Ethnic Studies Requirement Memo – Second Reading – amended and approved. APARC Report. EPC Report. SAC Report. CFA Report. Good of the Order.